Duck farming in Tamil Nadu – problems and prospects - S.R .Srininvsan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Duck farming is more gainful than chicken farming and mutually beneficial to both paddy and ducks in the integrated rice cum duck farming. However, even in certain places where the duck farming is in practice, the system of integrated rice-duck farming is not adopted. Hence, it was aimed to analyse the problems and prospects in duck farming so as to take suitable measures to address the issues and create awareness on rice cum duck cultivation in SST (Srinivasan Services Trust- CSR arm of TVS Motor Company, Chennai) adopted villages of Tamilnadu. Twenty five duck farmers and their flocks in SST adopted villages / hamlets of Thiruvallur and Thiruvannamalai districts of Tamil Nadu were the study materials. Socio-economic aspects of the farmers, adoption level of scientific methods including duck-rice / duck-fish rearing, economics and associated problems and prospects in duck farming were analysed. In the selected regions, only certain communities in BPL category (Below Poverty Line)are doing duck rearing under semi-intensive system as their family avocation. Most of them (84%) are nomadic, illiterate or school drop outs (80%) with family income varying from Rs.5000 -15,000 / month. There is no credit facility to these farmers from banking institutions. Mainly private money lenders financed their duck farming activity at a very high interest rate of 36% - 96% and their role existed at every stage of farming activity. Though adoption of scientific methods related to semi-intensive system is almost satisfactory, there is scope for further improvement in production. The economics of duck rearing worked out to Rs.7500 / month / 500 birds unit. Lack of credit facility from banking institutes, nonavailability of good quality ducklings, and lack of awareness on rice-duck / fish – duck integration are considered major issues in optimising production.